Instability of the distal radioulnar joint: medicine - Harbrecht, Andreas; Unglaub, Frank; Langer, Martin Franz; Müller, Lars Peter; Hug, Urs; Spies, Christian (Deutsches Ärzteblatt, 2025)
The hand is our most important tool. Certain structural injuries can result in instability of the wrist and, in particular, of the distal radioulnar joint (DRUJ), with serious consequences. Patients who have sustained such injuries usually present...
Gesehen am 30.09.2025